Design and interpretation of studies: relevant concepts from the past and some extensions - Cox, D. R. (2015)
Principles for the planning and analysis of observational studies, as suggested by W.G Cochran in 1972, are discussed and compared to additional methodological developments since then.Comment: 6 page